Кримінальна відповідальність медичних працівників за злочини проти життя та здоров’я особи: напрямки реформування законодавства - Цимбалюк, В.; Tsymbaliuk, V. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті висвітлюються проблемні питання кримінальної відповідальності медичних працівників за вчинення злочинів проти життя і здоров’я особи. Здійснено аналіз законодавчого регулювання кримінальної відповідальності медичних працівників за даний вид злочинів в зарубіжних країнах та сформульовано на цій основі пропозиції, спрямовані на вдосконалення законодавства України. КК України варото доповнити спеціальною нормою про позбавлення життя невиліковно хворої людини з мотивів жалю, визначивши спеціального суб’єкта даного злочину – медичного працівника. Також має бути криміналізовано медичну стерилізацію особи проти її волі. The article highlights the problematic questions of medical personnel criminal responsibility for crimes against human life and health. Crimes committed in connection with the provision of medical care, encroaching on the most important benefit of man – his life and health, which according to Art. 3 of the Constitution of Ukraine are the most important social values. Providing criminal legal means of human life and health, being implementation of the requirements of Art. 49 of the Constitution of Ukraine, is one the priority directions of the state. Following features of given category of offenses are allocated: firstly, they pose a threat to cause or causing factual harm to the life or health of the person (s), secondly, they are exposed to a special subject – health care personnel performing professional duties with medical care and health services, thirdly, these crimes may be deliberate and careful, fourthly, the victims of these offenses are patients. It is indicated that the establishment of criminal responsibility of medical workers is intended to provide criminal legal protection of human life and health of criminal violations of professional duties of medical workers. This should always be specific service functions of health workers, which relies on a special duty - taking care of human life and health. Proposals aimed at improving the legislation of Ukraine were formulated. In particular, it is proposed to distinguish new corpus delicti against human life and health of patients, which will contribute to improvement the classification of crimes, and the establishment, and the establishment of adequate criminal responsibility is now available eliminate gaps in the regulation of this aspect, since the current criminal law does not correspond to the objective needs of volume and patients' rights.
Criminal Responsibility of Medical Personnel for Crimes Against Life and Health: Law Reform Directions.
Keywords: медичний працівник; кримінальна відповідальність; злочини проти життя та здоров’я особи; евтаназія; штучне переривання вагітності; medical personnel; criminal liability; crime against human life and health; euthanasia; abortion